Carbon Sequestration of Limestone Mine Waste through Mineral Carbonation and Utilization as Supplementary Cementitious Material - M. Molahid, Verma Loretta; Mohd Kusin, Faradiella; Nurfakhira Meor Ahmad Kamal; Syed Hasan, Sharifah Nur Munirah; Ramli, Noor Allesya Alis; Abdullah, Ahmad Makmom; Ashaari, Zulfa Hanan (International Journal of Integrated Engineering, 2021)
This study highlights the potential of limestone mine waste for mineral carbonation and its potential as supplementary cementitious material. Mineralogical and chemical composition analysis of limestone mine waste sample were performed, and mineral carbonation experiment was conducted under ambient pressure and temperature. The effect of particle size and pH condition was investigated to observe the influence of the parameters on carbonation efficiency. The limestone mine wastes were identified to have potential for carbon sequestration due to its high calcium oxide content alongside magnesium oxide which are derived from Ca- and Mg-carbonate minerals. It can be seen from this study that smaller particle size and pH 10 condition were ideal for the carbonation process. The end product of calcium carbonate proved that mineral carbonation occurred during the reaction, indicating the potential of the mine waste as feedstock for mineral carbonation. Additionally, the use of limestone mine waste can also be regarded as supplementary cementitious material due to its chemical composition while at the same time serves as potential storage and sink for sequestered carbon dioxide.